Workforce development and skill formation in Asia - Benson, John, 1948-; Gospel, Howard F.; Zhu, Ying, 1961- (Routledge studies in the growth economies of Asia, 2013)
"Asia has undergone rapid transformation over the past several decades as many countries have embraced new technologies and the processes of globalisation. Focusing on a number of developed and developing Asian economies, this book explores the dynamics of workforce development and skill formation, and considers questions of both skills shortages and skills gaps"--